Inhomogeneous crystallization of a‐Si thin films irradiated by femtosecond laser. (5th March 2019) - Li, Dongyang; Ilyas, Nasir; Song, Yuhao; Zhong, Hao; Li, Wei; Jiang, Yadong
Abstract: Recently, we have carried out a detailed Raman analysis to investigate the inhomogeneous crystallization of a‐Si thin films irradiated by femtosecond (Fs) laser. As expected, there are many etched spots overlapping each other, which features the surface morphology of the irradiated films. It is observed clearly that there has generated an inhomogeneous crystallization inside a‐Si thin film induced by Fs laser, and the crystalline volume fraction in one irradiated spot varies depending on different areas from the center to the edge. It is hard to observe any crystallization at the spot center where maximum energy of Fs laser is injected; however, there is an increasing crystalline volume fraction when the site varies from the center to the edge of the irradiated spot. More importantly, as the site varies from the center to the edge, the TO mode of Si nanocrystals (NCs; first‐order Si–Si peak at 520.5 cm −1 ) is asymmetrically broadened towards the low wavenumber and exhibits a dip on the high wavenumber. A model has been proposed to explain this inhomogeneous crystallization inside the a‐Si thin films induced by Fs laser, and both phonon confinement model and Fano model have been employed to discuss the origin of asymmetric line shapes of TO mode of Si NCs, and we prefer to attribute the asymmetry of TO mode to Fano effect. Our present research results provide a deep insight into the origin of asymmetric broadening for the Raman TO mode of Si NCs inside a‐Si thin films irradiated by Fs laser. Abstract : There has generated an uneven crystallization inside a‐Si thin film induced by femtosecond laser, and the crystalline volume fraction in one irradiated spot varies from the central to the edge. It is found that the irradiated a‐Si film has a bilayer structure that is composed of a top Si nanocrystals layer and a bottom a‐Si layer. The TO mode of Si nanocrystals is asymmetrically broadened towards low wavenumber. We prefer to attribute the asymmetry of TO mode to Fano effect.